From arthritis to central sensitization: targeting the neuro-immune axis via microglial modulation in acupuncture treatment for Juvenile Idiopathic Arthritis–associated pain - Chen, Hang; Xu, Jixiang; Zhang, Xia (Frontiers in Immunology, 2026)
Juvenile Idiopathic Arthritis (JIA) is a common chronic rheumatic disease in children, and its associated persistent pain severely impacts the quality of life of affected patients. The severity of JIA-associated pain often does not correlate with the degree of peripheral inflammation, suggesting that Central Sensitization is a key underlying mechanism specific to JIA subtypes. At the core of this process is a dysregulation of the neuro-immune axis, particularly the aberrant activation of microglia within the central nervous system. As a non-pharmacological therapy, acupuncture demonstrates significant potential for JIA pain management, supported by a series of clinical studies. This review focuses on JIA-specific neuro-immune pathophysiology of chronic pain and systematically elucidates the complete pathway from peripheral inflammation to central microglial activation and central sensitization. By integrating evidence from both preclinical and clinical JIA studies, we provide a detailed analysis of how acupuncture remodels neuro-immune balance through mechanisms spanning peripheral autonomic regulation and central glial modulation. This modulation encompasses the inhibition of upstream pro-inflammatory signaling pathways. These include peripheral anti-inflammatory effects via the vagus nerve, regulation of systemic immunity, and direct inhibition of central microglial activity toward an anti-inflammatory phenotype. This work establishes a theoretical framework, grounded in JIA-specific neuro-immune pathophysiology, for acupuncture’s application in treating JIA-associated pain, highlighting its role in reducing reliance on analgesics.